Metodología activa y su incidencia en la comprensión lectora, de los estudiantes de la Unidad Educativa Adolfo María Astudillo cantón Babahoyo, provincia los Ríos - Briones Zuñiga, Karla América (2017)
This final work indicates how the active methodology allows to develop meaningful learning; here the student is the protagonist of his own learning and the teacher, a facilitator of this process. To encourage the development of competences, activities such as personal or group tasks are developed, which develop critical thinking, creative thinking as well as effective communication; the objective was to analyze the contribution of the active methodology in reading comprehension. The investigative work is explorative, descriptive and explanatory, applied to a sample of 5 teachers and 190 Sixth grade students, they were applied surveys, obtaining the following conclusions have no reading habits, parents do not supervise the work at home, Little use the motivation and reflection in the reading process, present difficulties to extract ideas from the text, read and reread to understand and memorize, poor interpretative and argumentative capacity, do not recognize the importance of ideas and can not order sequences. It is recommended to apply active strategies within reading through motivation, creativity, imagination, create reading habits, develop pedagogical innovations, apply reading levels, application of teaching resources, train teachers in strategies, techniques and processes.